Esophageal perforation caused by external air-blast injury - Wu Ming-Ho (Journal of Cardiothoracic Surgery, 2010)
Abstract Background Esophageal perforation after external air-blast trauma is rarely presented in the emergency room. The diagnosis is often delayed more than 24 hours. Methods We review the literature and report a case of esophageal perforation caused by external air-blast injury. Results Including the present case, a total of 5 cases of esophageal perforation were caused by external air-blast injury in English literature. Of them, the common presentations were chest pain and dyspnea. The treatment methods varied with each case. One patient died before diagnosis of esophageal perforation and the others survived after proper surgical management. Conclusions Early diagnosis and proper surgical management can reduce the morbidity and mortality of patients who suffered from esophageal perforation caused by external air-blast injury.